IMPROVING WRITING SKILL OF RECOUNT TEXT THROUGH GIVING CHAIN AND QUESTIONS TECHNIQUES IN SMAN 3 TEBING TINGGI - Puji Dwi Sulastri (Edu-Ling: Journal of English Education and Linguistics, 2019)
This classroom action research aims to improve students' skills in writing recounts using chain drawing techniques and several questions.The subjects of this study were students X IIS.1 SMA 3 TEBING TINGGI 2017/2018 lessons, amounting to 22 people consisting of 11 men and 11 women.In collecting data, recount writing and observation or observation tests are conducted.All data are collected and analyzed. In analyzing the results of the tests using a system scale the rating criteria are referent values. The results that the researchers obtained from this study were qualitative data and quantitative data.Qualitative data shows that students are very active and fluent in writing recounts, this can be seen by the increase in student activity in doing their own writing recount activities in the first cycle and second cycle, and students smoothly answer questions based on the images set out in recount essays.Whereas from quantitative data, it can be seen that there is an increase in the value of students from the level or level of information written on their recount.The number of students who get A in the first cycle is 1 meeting (1 person), 2nd meeting (2 people), and 3rd meeting (4 people). On the second cycle of the 1st meeting (9 people), 2nd meeting (17 people) and 3rd meeting (22 people). Students who get B score in cycle 1, meeting 1 (4 people), meeting 2 (4 people) and meeting 3 (12 people). On cycle 2, meeting 1st (6 people), 2nd meeting (5 people) and no B value at 3rd meeting. This means giving serial images and several questions, so that the writing skills of students X IIS.1 of SMA Negeri 3 Tebing Tinggi can be improved.